Toward a conceptual framework of the acceptability of tuberculosis treatment in children using a theory generative approach - Dillon T. Wademan; Megan Palmer; Susan Purchase; Marieke M. van der Zalm; Muhammad Osman; Anthony J. Garcia-Prats; James A. Seddon; H. Simon Schaaf; Anneke C. Hesseling; Ria Reis; Lindsey J. Reynolds; Graeme Hoddinott (PLOS Global Public Health, 2022)
To describe an early-stage holistic framework towards evaluating factors that impact the overall acceptability of TB treatment along the TB care cascade in children. We developed a conceptual framework utilising a theory generative approach. Domains were developed through review of existing definitions and analysis of existing qualitative data undertaken in acceptability studies of TB treatment in children. Clarity of domain definitions was achieved through iterative refinement among the research team. Three domains, each comprising several dimensions, were identified to holistically evaluate treatment acceptability: (1) usability, which involves the alignment between the requirements of treatment use and caregivers’ and children’s ability to integrate TB treatment into their everyday routines, (2) receptivity, which describes the end-user’s perception and expectations of treatment and its actual use, and (3) integration, which describes the relationship between available health services and caregivers/children’s capacity to make use of those services. Our framework addresses the gaps in current research which do not account for the influence of caregivers’ and children’s contexts on TB treatment uptake and overall acceptability. This approach may support the development of more standard, holistic measures to improve TB treatment delivery and experiences and future research in children.